2017
DOI: 10.1136/bmjopen-2016-013626
|View full text |Cite
|
Sign up to set email alerts
|

Soil transmitted helminthiasis in indigenous groups. A community cross sectional study in the Amazonian southern border region of Ecuador

Abstract: BackgroundRural communities in the Amazonian southern border of Ecuador have benefited from governmental social programmes over the past 9 years, which have addressed, among other things, diseases associated with poverty, such as soil transmitted helminth infections. The aim of this study was to explore the prevalence of geohelminth infection and several factors associated with it in these communities.MethodsThis was a cross sectional study in two indigenous communities of the Amazonian southern border of Ecua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
1
12
2
Order By: Relevance
“…We found no significant association between behavioural, service-related, and environmental factors in this study area. This is contrary to other studies [15,21,30,31]. In the current study, the socioeconomic characteristics of an individual were the main drivers of worm infestation.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We found no significant association between behavioural, service-related, and environmental factors in this study area. This is contrary to other studies [15,21,30,31]. In the current study, the socioeconomic characteristics of an individual were the main drivers of worm infestation.…”
Section: Discussioncontrasting
confidence: 99%
“…Children who lived in urban areas were more prone to infection than children who lived in rural areas. Another study found urban areas to be more prone to infection than rural area [21,25]. This could be explained by the fact that Chililambobwe district is mostly peri-urban with poor sanitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent national survey of STH prevalence in Ecuador that studied a representative sample of schoolchildren estimated a national prevalence of 28%, considerably lower than previous estimates, reflecting substantial progress over the previous 10 years in achieving the millennium development goals. However, the Amazon region of Ecuador continued to have high prevalence rates (59%) reflecting the relative isolation of this population that continues to suffer high levels of poverty…”
Section: Soil‐transmitted Helminthsmentioning
confidence: 99%
“…Maps specific for STH have been developed in different countries in order to determine areas at risk for the presence of these parasites, most of them using historical prevalence data from either point studies [14][15][16][17] or national STH data [18], but none of these were conducted at the household level. Most studies conducted at the household level have determined certain risk factors for infection with STH, but environmental parameters were not included [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%